Effects of Remnant Tissue Preservation on the Tendon Graft in Anterior Cruciate Ligament Reconstruction: A Biomechanical and Histological Study. (July 2016) - Takahashi, Tsuneari; Kondo, Eiji; Yasuda, Kazunori; Miyatake, Shin; Kawaguchi, Yasuyuki; Onodera, Jun; Kitamura, Nobuto
Background: There is controversy regarding the efficacy of remnant tissue preservation on graft healing in anterior cruciate ligament (ACL) reconstruction. Hypothesis: The preserved remnant tissue will (1) adhere to the graft surface and undergo a remodeling process, (2) accelerate graft revascularization, (3) increase the number of graft mechanoreceptors by 4 weeks, and (4) improve anteroposterior knee laxity and structural properties of the graft by 12 weeks. Study Design: Controlled laboratory study. Methods: Forty-two sheep were randomly divided into 2 groups of 21 animals. In group I, the ACL was completely removed. In group II, the ACL was transected at the midsubstance but not debrided. ACL reconstruction was performed using a semitendinosus tendon autograft in both groups. Histological changes of the grafted tendon and the remnant tissue were evaluated at 4 and 12 weeks after surgery. Biomechanically, anterior translation and knee joint stiffness under an anterior drawer force and the structural properties of the femur-graft-tibia complex were evaluated. Results: The preserved remnant tissue was histologically distinct from the graft at 4 weeks, while the tissue partially adhered to the graft surface at 12 weeks. The ACL remnant tissue significantly accelerated revascularization in the grafted tendon at 4 weeks and significantly increased the number of mechanoreceptors at 4 and 12 weeks. In addition, remnant preservation significantly improved anterior translation (9.3 ± 2.1 mm and 5.4 ± 1.7 mm at 60° of knee flexion in groups I and II, respectively) and knee joint stiffness at 12 weeks. However, there were no significant differences in the structural properties between the 2 groups at 4 and 12 weeks after surgery. Conclusion: Preservation of the ACL remnant tissue in ACL reconstruction enhanced cell proliferation, revascularization, and regeneration of proprioceptive organs in the reconstructed ACL and reduced anterior translation. However, remnant preservation did not improve the structural properties of the graft. Clinical Relevance: These results imply that preservation of the ACL remnant tissue may improve graft healing after ACL reconstruction.